PENYERTAAN METODE SOUS VIDE DALAM PENGOLAHAN STEAK DARI DAGING SAPI DAN DAGING AYAM - ., Sunar; Kalpikawati, Ida Ayu; Nasution, M. Nur A.; Rumadana, I Made (Pusat penelitian & Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2010)
The traditional cooking method has become classical cooking and nouvelle cuisine. Modern chefs collaborate with scientists have developed cooking technology, which is called Molecular Gastronomy. One of the sub of molecular gastronomy is sous vide (French word). Sous vide means vacuum and it is 'predicted to be the cooking for tomorrow. In this experiment, sous vide is applied to the cooking method of beef and chicken steak. The analysis technic used is descriptive base on organoleptic and chemical tests. It is found out that by using sous vide, beef & chicken steak become more juicy, more tender, bigger in volume, has less of baking aroma, less-fat and protein compared to he conventional steak. By the application of Sous-vide method in the preparation, it is possible to make mass product convenient food for franchise restaurant and catering.",